ENT 600 : H8phone / Wan Mohd Firdaus Wan Mohd Zaki … [et al.] - Wan Mohd Zaki, Wan Mohd Firdaus; Zulkafli, Muhamad Zulfadli; Mahmud, Luqman Khakim; Jaafar, Mohd Izzuan; Rosdi, Muhammad Fahmi (2015)
The product to be innovated is H8phone that eliminate the accumulated heat and pressure to the head as a result of prolongs usage of headphone. It also provide safety and comfort to users as it reduce the risk of hearing loss and ear infections. This product means to provide comfort to the user for long usage while eliminate heat that accumulate around the ear. The product also avoids pressure to the head to reduce possibilities of headache and dizziness.